OP0096 Relevance of the 6-Minute Walking Test in Assessing the Severity of Pulmonary Arterial Hypertension Associated with Systemic Sclerosis, without Interstitial Lung Disease. (10th June 2014) - Sanges, S.; Launay, D.; Sitbon, O.; Hachulla, E.; Mouthon, L.; Guillevin, L.; Rottat, L.; Clerson, P.; Cordier, J.-F.; Simonneau, G.; Humbert, M.
Abstract : Background: In patients with idiopathic pulmonary arterial hypertension (PAH), 6-minute walking test (6MWT) correlates well with the hemodynamic parameters like cardiac index and is a robust prognosis factor. In PAH associated with systemic sclerosis (SSc-PAH) however, data are more scarce and still a matter of debate. Various comorbidities caused by the underlying systemic disease (interstitial lung disease, musculoskeletal involvement, heart involvement, anemia, depression, ...) may be confounding factors, interfering with the interpretation of the 6MWT. Moreover, no study has evaluated the correlation between the 6MWT and the hemodynamics (i.e. the gold standard test to assess the severity of PAH) in this population yet. Objectives: The aims of this study were to assess whether there is a correlation between the initial 6MWT and the hemodynamic parameters measured during the right heart catheterization (RHC), in SSc-PAH patients without interstitial lung disease (ILD). Methods: Seventy-five patients with SSc-PAH and without any ILD on chest HRCT, prospectively enrolled in the French PAH Network, were included. Several data were collected at baseline regarding the clinical status (age, sex, BMI, NYHA functional class, SSc subtype), the 6WMT (total distance, heart rate (HR) and ΔHR, SaO2 and ΔSaO2, Borg score), the RHC (mRAP, mPAP, sPAP, dPAP, cardiac output and index, PVR, TPR, systolic stroke volume), the PFT (FEV1, FVC, TLC, DLCO/VA, PaO2, PaCO2) and the transthoracic echocardiography. The correlation of the 6MWT total distance with each hemodynamic parameter, but also with other data, was studied by linear regression. Results: Univariate analysis showed a statistically significant correlation between the 6MWT total distance and all the RHC hemodynamic parameters, especially the mPAP ( R 2 =0.10, p =0.0045), cardiac index ( R 2 =0.20, p <0, 0001) and PVR ( R 2 =0.18, p =0, 0001). A similar correlation was also found with age and NYHA class, especially classes 3&4. In multivariate analysis, the 6WMT total distance was significantly and independently correlated with the cardiac index ( R 2 =0, 26, p <0, 0001) and functional classes NYHA 3&4 ( R 2 =0, 08, p =0, 018). Those 2 parameters accounted for 34% of the 6MWT total distance, the cardiac index explaining the majority of this distance. Conclusions: To our knowledge, this study is the first to prove a correlation between the initial 6MWT total distance and the hemodynamic parameters of PAH severity, in SSc-PAH patients without ILD. It further establishes the relevance of this test in assessing the severity of the PAH in this population. Although potentially confounding comorbities are frequent, the 6MWT remains a relevant way to assess the severity of the PAH in SSc patients without ILD. However, other factors are probably involved in the 6MWT total distance, since the studied parameters accounted for only a third of it. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1378